Just a phrase i'm going through my life in language - Crystal, David, 1941-; Routledge (Firm) (Boca Raton, FL : Routledge, 2009)
Addresses the kinds of language-based questions that emerge literally everywhere and that pique the curiosity of linguists and non-linguists alike--transmitted to us through the wonderful wit, style, and personal perspective of David Crystal
Title from container
Keywords: Crystal, David, -- 1941-; Linguists -- Great Britain -- Biography; Linguistics -- Great Britain -- History -- 20th century; Scholars -- Great Britain -- Biography; Lexicographers -- Great Britain -- Biography